Rich dad poor dad what the rich teach their kids about money-- that the poor and middle class do not! - Kiyosaki, R.T (Scottsdale, Ariz Plata Publishing LLC, 2012)
Taking to heart the message that the poor and middle class work for money, but the rich have money work for them, the author lays out a financial philosophy based on the principle that income-generating assets always provide healthier bottom-line results